2016
DOI: 10.1097/mbc.0000000000000168
|View full text |Cite
|
Sign up to set email alerts
|

VKORC1 and CYP2C9 genotypes in Egyptian patients with warfarin resistance

Abstract: Warfarin is the most commonly prescribed anticoagulant drug; however, a narrow therapeutic range and a high risk of bleeding or stroke complicate its clinical use. Warfarin resistance was defined as prolonged warfarin requirements of more than 15 mg/day to achieve therapeutic anticoagulation or failure to achieve therapeutic anticoagulation with more than 20 mg/day. The resistance is associated with polymorphisms of the vitamin K epoxide reductase-oxidase complex (VKORC1) and cytochrome P450-2C9 (CYP2C9) genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In a preliminary study on 41 Egyptian pediatric patients receiving warfarin maintenance therapy, Kamel El-Din et al (11) found that age is the most significant determinant of the warfarin dose and that the presence of the CYP2C9 and VKORC1 gene polymorphisms does not affect the warfarin dose. In contrast, in a recent study on Egyptian patients, Azzam et al (24) suggested that the VKORC1-1639 GG and wild-type CYP2C9*1*1 genotypes are associated with high dose requirements during warfarin therapy and that VKORC1-1639 GG is responsible for warfarin resistance and failure. We considered CYP2C9 and VKORC1 genetic polymorphisms in addition to age and height, while the ideal dose requirements were calculated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In a preliminary study on 41 Egyptian pediatric patients receiving warfarin maintenance therapy, Kamel El-Din et al (11) found that age is the most significant determinant of the warfarin dose and that the presence of the CYP2C9 and VKORC1 gene polymorphisms does not affect the warfarin dose. In contrast, in a recent study on Egyptian patients, Azzam et al (24) suggested that the VKORC1-1639 GG and wild-type CYP2C9*1*1 genotypes are associated with high dose requirements during warfarin therapy and that VKORC1-1639 GG is responsible for warfarin resistance and failure. We considered CYP2C9 and VKORC1 genetic polymorphisms in addition to age and height, while the ideal dose requirements were calculated.…”
Section: Discussionmentioning
confidence: 88%
“…The FDA recommends that clinicians should consider genetic testing of CYP2C9 and VKORC1 polymorphisms in every patient before adjusting the warfarin dose (20,23). Although there are many studies in the literature on the impact of genetic polymorphisms on warfarin dose requirements in adult populations (14,16,20,22,24,25), there are only a few studies of pediatric populations (11)(12)(13). In children, data about the pharmacogenetics of warfarin are limited and inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from atrial fibrillation (AF), indications studied include stroke, prophylaxis associated with the use of artificial heart valves and continuous‐flow left ventricular assist devices, deep venous thrombosis and pulmonary embolism . Patients studied came from diverse ethnic/racial backgrounds and included not only adult but also paediatric populations …”
Section: Resultsmentioning
confidence: 99%
“…The FDA recommends that clinicians should consider genetic testing of CYP2C9 and VKORC1 polymorphisms in every patient before adjusting the warfarin dose ( 20 , 23 ). Although there are many studies in the literature on the impact of genetic polymorphisms on warfarin dose requirements in adult populations ( 14 , 16 , 20 , 22 , 24 , 25 ), there are only a few studies of pediatric populations ( 11 13 ). In children, data about the pharmacogenetics of warfarin are limited and inconsistent.…”
Section: Discussionmentioning
confidence: 99%